Chronic kidney disease in type 2 diabetes: treatment - Thomas, Merlin (Henry Stewart Talks, 2023)
Goals for treating T2D and CKD, Multifactorial management, SGLT2 inhibition, RAAS blockade, Statin therapy, Risk-factor management, Glucose control, Antihypertensive treatment, Further lipid lowering, Weight control, CV risk reduction, Albuminuria